Las noticias de la Comunidad Valenciana en televisión - Pomares Pastor, Ricardo Ángel (Estudios sobre el Mensaje Periodístico, 2010)
Research has tried to shed some light on how they are and how they have envolved the news of an autonomous community, in this case the Valencian, on the news of Telecinco, Antena 3 and TVE 1. The content analysis has examined the two editions daily, from Monday to Friday, during January 2004 and 2008. The results show that the Valencian Community are not represented as an autonomous entity. The visibility of the news is trivialized by a serialization of negative, anecdotal and dramatic events, in which emotion prevails over information.